Tension Between Domestication and Foreignization In English-Language Translations of Anna Karenina: Exploring the Evolution of Translation of Anna Karenina into English (Journal of Advances and Scholarly Researches in Allied Education, 2014)
One of the key issues in recent translation theories has been onwhether translation should domesticate or foreignism the source text.Domesticating translation as a replacement of the linguistic and culturaldifference of the foreign text with a text that is intelligible to the targetlanguage reader foreign zing translation is defined as a translation thatindicates the linguistic and cultural differences of the text by disrupting thecultural codes that prevail in the target language. Other scholars, likecriticize this dichotomy by pointing out that a translation may be radically orientedto the source text in some respects, but depart radically from the source textin other respects, thus denying the existence of the single polarity thatdescribes the orientation of a translation. In the present paper I try to showhow the history of translation of Anna Karenina into English reflects thesedifferent stages of evolution.